Shift Left Security - Gaurav Malik; Prashasti (Eastasouth Institute, 2025)
Shift Left Security is a proactive approach to software development that aims to integrate security measures at the beginning of the software development lifecycle (SDLC) and at the design and development phases. In the past, security for software development has been reactive, looking for vulnerabilities at the test or deployment stages. However, this method has proven ineffective in the face of the complexity of these modern software systems and the frequency of cyber-attacks. Shift Left Security instead highlights embedding security practices from the beginning to capture vulnerabilities and detect and remediate them at the very beginning before they even hit the production stage. Continuous security testing, early risk assessment, and real-time feedback loops to rectify vulnerabilities immediately, given that solving them is critical during development, are a part of the proactive model. Shift Left Security integrates security into the SDLC, ensuring the security posture of the software applications is strengthened, post-release remediation is reduced, and time to market is accelerated. The significant advantage of it is that it lets organizations open up to a conversation around security as early as possible without the risk of it becoming an issue. Shift Left Security is an area of interest that this study explores in terms of its principles, benefits, challenges, and tools. This serves as a valuable offering that offers a hands-on approach to adopting this approach by organizations to achieve more secure, resilient software products through improved development efficiency and better protection against emerging cyber threats.